Characteristics and Goals of Entrepreneurship-Based Education - Holilur Rahman; Muhammad Rosul; Muhammad Sofiullah; Ahmad Muta’ali (Penerbit Hellow Pustaka, 2024)
Poverty is a way of entry for the new century of colonialism. Future generations should be able to fight for this nation's wealth. The education of entrepreneurship is a way to reduce poverty; it is an education concept encouraging students to be creative and innovative in doing something. The pattern of such education requires learners to be productive. Entrepreneurship education is educational framework that directs learners to be quick in understanding and probing the economic and social needs of the surrounding community. Government should be willing to provide sufficient funds so that the process of entrepreneurship education can run smoothly.Even the community should be more active and intense in monitoring the development of entrepreneurial education if they want the progress of their nation, not only being a nation of coolie by sending migrant workers abroad, mostly of them are maid workers. This country is rich in natural resources, were it supported by resources having a high entrepreneurial spirit it would become a prosperous state so that by itself poverty would be far reduced. Poverty will evaporate into the history and transform to be memories that only can be remembered in museums.